Measureable Organization Value (MOV) pada Implementasi Sistem Informasi Manajemen Mutu Sekolah Kejuruan (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2017)
The implementation of information system product on the organization could be successful if it can achieve Measureable Organization Value (MOV). This research aimed for measuring the achievement of MOV on the implementation of IS in Vocational High School Quality Assessment Information System. MOV statement that is used as benchmarking was efficiency of human resource performance after the 6 months implementation. The subjects of this research were five schools that had not implemented quality assurance management information systems. The object under study is the improvement of human resource performance after the implementation of IS in vocational high school. The descriptive quantitative technique is used in this research as a technique to analyze and obtain the data. Direct cutover used as an implementation scenario of quality assurance management information system in 5 vocational high schools. Data about human resource performance obtained by using questionnaire, interview and observation. The result of this research showed that there was an increase in the efficiency of human resource performance in managing the quality assurance of 5 vocational high school by 59.25% from 6 months of implementation. Vocational high school needs to improve the satisfaction factor by increasing usefulness, efficiency, and effectively through updates to its systems and regulations. As a conclusion, vocational high school management information systems can continue to be used because of the achievement of its MOV.